Georgia Architectural and Historic Properties Survey of Rural [032] Quitman - Morven Rd., Ga. December 1980 - Smith and Bartholomew (South Georgia Area Planning and Development Commission, 1980)
Georgia Architectural and Historic Properties Survey of Rural [032] Quitman - Morven Rd., Ga. December 1980. L-shaped house with gabled tin roof. Square posts at shed porch. Double hung sash windows with 6/6 lights. Exterior chimney. Smokehouse on right. Small outbuildings. Faces road. Poor condition. Date of Construction: c. 1890. Typical farmhouse in rural Brooks Co. area.
Georgia Architectural and Historic Properties Survey of Rural [032] Quitman - Morven Rd., Ga. December 1980. 1 electronic record and assets. Digitized from originals. 1 PDF. 1 scan. 1 photograph. 2400 DPI TIF. 300 DPI 4x6 JPG. 1.44 MB (1,516,817 bytes).
Keywords: Historic buildings; Real property surveys; Brooks County (Ga.); Lowndes County Historical Society (Lowndes County, Ga.); Quitman (Ga.)